Mental health status and coping strategies during COVID-19 pandemic among university students in Central Serbia - Radovanovic, Jovana; Selakovic, Viktor; Mihaljevic, Olgica; Djordjevic, Jelena; Čolović, Sofija; Djordjevic, Jelena R.; Janjic, Vladimir; Jovicic, Milena; Veselinovic, Sladjana; Vukomanovic, Ivana Simic; Janicijevic, Katarina; Slovic, Zivana; et al. (Frontiers in Psychiatry, 2023)
The objective of this research was to evaluate the occurrence of depression, anxiety, and stress, as well as the level of life contentment and coping mechanisms employed by college students amidst the Covid-19 pandemic.: A total of 588 students of the Faculty of Mechanical Engineering and the Higher School of Medicine, Kraljevo, University of Kragujevac, Central Serbia, participated in an online cross-sectional survey in the period September-October 2022. Depression Anxiety Stress Scales (DASS-21) was used to measure the levels of depression, anxiety, and stress. The Coping Questionnaire -a shorter version (Brief Cope Inventories) assesses the coping strategies a person uses in stressful situations, and the 5-item Life Satisfaction Scale is used to examine the level of life satisfaction.The symptoms of depression were reported by 34.9%, of anxiety by 47.1% and of stress by 44.2%. The type of faculty (p=0.001), and place of residence (p=0.036) correlated with depression, gender with anxiety (p=0.001) and stress (p=0.015). In terms of coping mechanisms, the most frequently mentioned strategies, based on average scores, were acceptance (5.76), positive interpretation (5.55), humor (5.46).The adverse impact of COVID-19 was a risk factor for depression, anxiety and stress symptoms. A negative correlation exists between the levels of depression, anxiety, and stress, and the overall life satisfaction of university students. Offering the necessary assistance through psychological interventions and effective coping techniques is crucial in ensuring the optimal mental health of university students.